2012
DOI: 10.2527/jas.2010-3240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding modified distillers grains plus solubles on marbling attributes, proximate composition, and fatty acid profile of beef1,2

Abstract: Wet distillers grains contain approximately 65% moisture. A partially dried product [modified distillers grains plus solubles (MDGS)] contains about 50% moisture. However, both have similar nutrient composition on a dry matter basis. The objective of this study was to investigate the effects of finishing diets varying in concentration of MDGS on marbling attributes, proximate composition, and fatty acid profile of beef. Yearling steers (n = 268) were randomly allotted to 36 pens, which were assigned randomly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
1
14
1
Order By: Relevance
“…For example, substituting wheat (Aldai et al, 2010a;Dugan et al, 2010) or triticale (He et al, 2014) DDGS for barley grain was reported to reduce total t-18:1 and t10-18:1 whereas substituting corn DDGS for barley grain increased total t-18:1 and t10-18:1 (Aldai et al, 2010a). Several studies also reported increases in proportions of total and individual t-18:1 FA in beef when substituting corn DDGS for whole grains (Gill, Vanoverbeke, Depenbusch, Drouillard, & Dicostanzo, 2008;Mello et al, 2012;Vander Pol, Luebbe, Crawford, Erickson, & Klopfenstein, 2009). These findings suggest that substituting DDGS from small grain as opposed to DDGS from large grains for whole grains produces a more desirable t-18:1 isomeric profile in beef.…”
Section: Addition Of Non-forage Fibre Sourcesmentioning
confidence: 87%
“…For example, substituting wheat (Aldai et al, 2010a;Dugan et al, 2010) or triticale (He et al, 2014) DDGS for barley grain was reported to reduce total t-18:1 and t10-18:1 whereas substituting corn DDGS for barley grain increased total t-18:1 and t10-18:1 (Aldai et al, 2010a). Several studies also reported increases in proportions of total and individual t-18:1 FA in beef when substituting corn DDGS for whole grains (Gill, Vanoverbeke, Depenbusch, Drouillard, & Dicostanzo, 2008;Mello et al, 2012;Vander Pol, Luebbe, Crawford, Erickson, & Klopfenstein, 2009). These findings suggest that substituting DDGS from small grain as opposed to DDGS from large grains for whole grains produces a more desirable t-18:1 isomeric profile in beef.…”
Section: Addition Of Non-forage Fibre Sourcesmentioning
confidence: 87%
“…Conversely, D3 carcasses were lower in fat content as expected (Canada Gazette 2007; Canadian Beef Grading Agency 2016). Intramuscular fat content of the LT is well correlated with marbling score at the grade site (Li et al 2006;Mello et al 2012). The pattern of intramuscular fat content in the muscles was similar to the marbling score differences observed at the grade site in the same animals (Rodas-González et al 2013), in which the D4 grade obtained the highest marbling scores (543), followed by D1 (517), D2 (491), and OTM (448), next by UTM (424), and finally D3 with the lowest marbling score (272).…”
Section: Muscle Weightsmentioning
confidence: 99%
“…However, when evaluated by trained sensory panelists, there were no differences reported for flavor, tenderness, juiciness, or overall satisfaction (Moody et al, 1970). Other researchers have evaluated marbling texture; however, comparisons were not made among the marbling texture groups in most of these studies (Goll et al, 1965;Cross et al, 1975;Cross, 1977;Dubeski et al, 1997;de Mello et al, 2012ade Mello et al, , 2012bDurunna et al, 2014). Therefore, the objective of the current study was to evaluate the effects of marbling texture on consumer and trained sensory panel ratings of beef strip loins varying in marbling texture (fine, medium, and coarse) from 3 USDA quality groups.…”
Section: Introductionmentioning
confidence: 96%
“…www.meatandmusclebiology.com both levels (Smith et al, 2001). Marbling texture is impacted by a variety of factors including breed Yang et al, 2006;Albrecht et al, 2011) and animal diet (Dubeski et al, 1997;de Mello et al, 2012a, b;Durunna et al, 2014). But marbling texture's impact on beef palatability is unclear as it has not been the primary focus of much previous work.…”
Section: Marbling Texturementioning
confidence: 99%